Keberkesanan Pasukan Maya di Malaysia: Satu Tinjauan dalam Organisasi Bertaraf Koridor Raya Multimedia (MSC) yang Terpilih (Sains Humanika, 2014)
The main focus of the study is to identify the factors that influence the effectiveness of virtual teams in organizations selected MSC. Conceptual framework based on System Theory by Lipnack & Stamps (2000), Virtual Team Effectiveness Model by Lurey & Raisinghani (2001) Â and Koay Hooi Ling (2003). Quantitative method used and 363 questionnaires distributed to experienced staff working in virtual teamwork in organization MSC in Kuala Lumpur, Selangor, Penang and Kedah. Data were analyzed using inferential statistics through SPSS. Regression analysis showed the internal dynamics of the team in terms of frequency of use of communication media team (fax, e-mail, and share database system), the internal dynamics of the team in terms of team relationships (relationship among team members, relationship leader and team members, trust team), diversity work practices and team recognition that contribute significantly and positively to the effectiveness of virtual teams.
Keywords: Virtual teams; the effectiveness of virtual teams